NK Cells Contribute to the Immune Risk Profile in Kidney Transplant Candidates - DeWolfe, David; Aid, Malika; McGann, Kevin; Ghofrani, Joshua; Geiger, Emma; Helzer, Catherine; Malik, Shaily; Kleiboeker, Steve; Jost, Stephanie; Tan, Chen Sabrina (Frontiers in Immunology, 2019)
Background: A previously proposed immune risk profile (IRP), based on T cell phenotype and CMV serotype, is associated with mortality in the elderly and increased infections post-kidney transplant. To evaluate if NK cells contribute to the IRP and if the IRP can be predicted by a clinical T cell functional assays, we conducted a cross sectional study in renal transplant candidates to determine the incidence of IRP and its association with sepcificNK cell characteristics and ImmuKnow® value. Material and Methods: 65 subjects were enrolled in 5 cohorts designated by age and dialysis status. We determined T and NK cell phenotypes by flow cytometry and analyzed multiple factors contributing to IRP. Results: We identified 14 IRP+ (CMV seropositivity and CD4/CD8 ratio < 1 or being in the highest quintile of CD8+ senescent (CD28-/CD57+) T cells) individuals equally divided amongst the cohorts. Multivariable linear regression revealed a distinct IRP+ group. Age and dialysis status did not predict immune senescence in kidney transplant candidates. NK cell features alone could discriminate IRP- and IRP+ patients, suggesting that NK cells significantly contribute to the overall immune status in kidney transplant candidates and that a combined T and NK cell phenotyping can provide a more detailed IRP definition. ImmuKnow® value was negatively correlated to age and significantly lower in IRP+ patients and predicts IRP when used alone or in combination with NK cell features. Conclusion: NK cells contribute to overall immune senescence in kidney transplant candidates.